The Prevention and Control of Pests through Plant Quarantine in India with Special Reference to J&K: Problems and Perspectives - Bilal Ahmad Bhat; Fareed Ahmed Rafiqi; Nazia Fayaz; Hina Basharat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The idea of prevention and control of pests and insects injurious to agricultural production, storage and growth existed prior to the independence. There was a need to update the law in this direction which lead to the passing of Destructive Insects and Pests (Amendment) Act 1992. It was further reinforced by The Plant Quarantine Order, 2003, which puts restrictions on import of plants or plant material unless permitted by the Plant Protection Adviser (PPA) based on the international standards. Quarantine specifically provided for a legal restriction on movement of agricultural commodities for the purpose of exclusion, prevention or delay in the establishment of plants, disease or parasites in the area where they are not present. So a new pest, after arrival and establishment, can rapidly develop into destructive proportions. Plant pest epidemics could result in the loss of agricultural produce. This may adversely affect the food production or an existing export trade. In J&k the apple, saffron, paddy and other agro-products have been badly affected by the import of insecticides, pesticides and foreign imported plants , so the need for quarantine becomes all the more important. The research institutions are developing techniques of new varieties of plants and seeds to supplement the fragile biosphere of the territory but the potential threat to spread disease is there. In this paper an attempt is made to assess and evaluate the mechanism of quarantine to safeguard the flora and fauna of the territory.